An ionic liquid as a potential multifunctional lubricating oil additive. (17th November 2018) - Talukdar, Sujit; Ghosh, Pranab
Abstract: Homopolymer of decyl acrylate was synthesized and blended with phosphonium based ionic liquid and their characterisation was carried out by spectral method (NMR, IR), thermogravimetric analysis and gel permeation chromatography (GPC). Performance of these blends were evaluated by standard ASTM method in base oil which clearly indicates that the blend effectively act as anti-wear agent and also pour point depressants and viscosity modifiers. A comparison of their performances with homopolymer has also been evaluated and reported.